Impacts of Food‐Based Flock Size on Foraging Patterns, Activity Time Budget and Foraging Efficiency: Flexible Behavioral Responses of the Wintering Oriental Storks (Ciconia boyciana) to Changes in Aquaculture at Shengjin Lake, China - Lei Cheng; Lizhi Zhou; Chao Yu; Yiwei Bao (Ecology and Evolution)
ABSTRACT Food resources, as key limiting factors for wintering waterbirds, influence their habitat selection patterns and foraging behaviors. Meanwhile, seasonal fluctuations in water levels and human exploitation of lake wetlands both affect the availability of food. Therefore, knowledge of the spatio‐temporal dynamics of habitat utilization and adaptive behavior strategies can provide insights into how animals adapt to habitat changes in wetlands and has important conservation implications. In this study, we examined the effect of dynamic food resource supply on the spatial patterns, activity budget, and foraging strategy of Oriental Storks (Ciconia boyciana) at Shengjin Lake in China during a period where extensive fishing nets were present limiting the movement and dispersal of waterbirds (“pen culture period, PP” in 2017 winter) and a period after the removal of these pens during wetland restoration (“non‐pen culture period, NPP” in 2018 winter). In comparing with the wintering storks in NPP, we demonstrated an overall loss of range and a significant reduction in population size in PP, which were probably due to habitat alteration and fragmentation triggered by pen culture. We reported that a higher overall time budget in foraging and locomotion and a comparatively lower in other behaviors with storks in PP. Net pens resulted in limited activity areas of the storks and a reduction in food availability due to habitat alteration and fragmentation, thus resulting in a more flexible and radical trend in the foraging patterns of the wintering storks was triggered by the combined effects of the net pens removal and habitat connectivity in NPP. Pen culture had resulted in a more conservative foraging strategy and a homogenization of behavioral composition for wintering storks at the lake. Our study highlighted the behavior‐based results may provide key information to conceive management and conservation plans for wintering waterbirds.